Komitmen Sebagai Mediator Pengaruh Iklim Inovatif dan Kecocokan Individuâ€Tim Terhadap Kinerja - Sugiyanto, - (Jurnal Psikologi, 2009)
In the long term, the purpose of the research is to build an understanding of the organizational commitment as an important mediator of the effects of various antecedents on performance. The commitment as a mediator has been studied in various levels of workplace: Low, medium, and high technologies. The current study tested a theoretical model of the components of organizational commitment as mediators, innovative climate and personâ€team fit as antecedents, whereas its consequence was performance. The components of organizational commitment were affective, continuance, and normative. All of the measures applied a 5â€point scale response ranging from 1 (not very important at all or strongly disagree) to 5 (very important or strongly agree). Respondents were 203 university students. Data was analyzed using hierarchical multiple regression analyses.Results showed that the three components of organizational commitment were not significant mediator of the effects of innovative climate and personâ€team fit on performance. Theoretical and methodological rinterpretations were discussed regarding the next designs of study.